Human genetics : concepts and applications - Lewis, Ricki (Dubuque, Iowa : Wm. C. Brown, 1994)
A non-science majors human genetics text that explains what genes are, how they function, how they interact with the environment, and how our understanding of genetics has changed since completion of the human genome project. This book is useful for citizens who are responsible for evaluating foods, and technologies in the age of genomics.
Includes bibliographical references and index.
Keywords: Human genetics; Genetics, Medical